The black goby Gobius niger Linnaeus, 1758 in the Marchica Lagoon (Alboran Sea, Morocco): spatio-temporal distribution, its environmental drivers, and the site-related footprint - LAMKHALKHAL, AMAL; SELFATI, MOHAMED; RAHMOUNI, IMANE; KADDOURI, NASSIR; BADAOUI, BOUABID; PARISELLE, ANTOINE; BENHOUSSA, ABDELAZIZ; KOVAČIĆ, MARCELO; KMENTOVÁ, NIKOL; VANHOVE, MAARTEN P.M.; BAZAIRI, HOCEIN (Mediterranean Marine Science, 2024)
Gobies (Gobiidae) are well represented in the Marchica Lagoon on the Moroccan Mediterranean coast, both in terms of species richness and in terms of abundance, with the black goby, Gobius niger Linnaeus, 1758, being the dominant species. The present study aims to examine (1) the spatial and temporal distribution of G. niger and its environmental drivers in the lagoon and (2) the potential lagoon-related footprint using morphometric, genetic, and parasitological proxies. Systematic monthly sampling covering the whole lagoon basin performed between October 2015 and September 2016 revealed a year-long presence of G. niger throughout the lagoon with significantly low densities in winter. The highest abundances were recorded in the shallow bottoms of the lagoon’s inner margins on a variety of substrates (mud, muddy-sand, sandy-mud, and fine sand) mostly covered by macroalgae and/or seagrass meadows. Depth was revealed to be the most important predictor of the distribution of the black goby in the lagoon. It should, however, be regarded as a variable that acts synergistically with other factors, such as temperature, vegetation cover, and the sediment’s mean grain size. Comparison of black goby populations from the lagoon with their conspecifics from the adjacent Mediterranean coast of Morocco revealed that specimens caught at sea are larger than those of the lagoon population. Of the 180 gobies investigated, not a single one hosted the parasites we targeted in the parasitological approach, monogenean flatworms. The absence of population structuring, low genetic diversity, and the presence of common haplotypes indicate no apparent restriction in the gene flow between the two populations. Therefore, the observed morphometric differences seem to be due to external environmental conditions rather than genetic differences.